Mutations in the EXT1 and EXT2 genes in Spanish patients with multiple osteochondromas - Sarrión, P. (2013)
Multiple osteochondromas is an autosomal dominant skeletal disorder characterized by the formation of multiple cartilage-capped tumours. Two causal genes have been identified, EXT1 and EXT2, which account for 65% and 30% of cases, respectively. We have undertaken a mutation analysis of the EXT1 and EXT2 genes in 39 unrelated Spanish patients, most of them with moderate phenotype, and looked for genotype-phenotype correlations. We found the mutant allele in 37 patients, 29 in EXT1 and 8 in EXT2. Five of the EXT1 mutations were deletions identified by MLPA. Two cases of mosaicism were documented. We detected a lower number of exostoses in patients with missense mutation versus other kinds of mutations. In conclusion, we found a mutation in EXT1 or in EXT2 in 95% of the Spanish patients. Eighteen of the mutations were novel.